A multifunctional metasurface with integrated absorption and polarization rotation. (15th October 2018) - Zhou, Yulong; Cao, Xiangyu; Gao, Jun; Yang, Huanhuan; Zheng, Yuejun; Li, Sijia
Abstract: A multifunctional metasurface with integrated absorption and polarization rotation is proposed and investigated. The unit cell is composed of a cross arrow in the middle and a square loop on the outside loaded with four-sided lumped resistors. The absorption is mainly achieved by the outside resistor-loaded loop, and the polarization rotation is obtained in virtue of the combination of the outside loop and the central asymmetric structure. Simulated results show that the proposed metasurface obtains a polarization-insensitive absorption from 4.2 GHz to 5.0 GHz, a wideband linear-to-linear polarization rotation from 11.65 GHz to 16.10 GHz and a linear-to-circular polarization rotation from 17.7 GHz to 20 GHz. To verify the design, the proposed metasurface is fabricated and measured. The experimental results agree well with the simulated results.